A multi-layer perfect wave-absorbing cement board

By introducing carbon nanotubes as the dielectric layer of the metasurface structure of the conductive surface in building materials, combining metasurface technology and cement-based materials to design a multi-layer perfect wave-absorbing cement sheet, solving the existing building wave-absorbing materials The problem of limited wave absorption performance achieves the effect of efficient absorption of electromagnetic waves in a wide frequency range.

CN113285231BActive Publication Date: 2025-02-07ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110459202.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-27
Publication Date
2025-02-07
Estimated Expiration
2041-04-27

AI Technical Summary

Technical Problem

The existing building absorbing materials have limited wave absorption performance, making it difficult to achieve efficient absorption within a wide frequency range, and the preparation process is complex, which cannot meet the load-bearing and durability requirements of building structures.

Method used

By using carbon nanotubes as the dielectric layer of the metasurface structure of the conductive surface, combining metasurface technology and cement-based materials to design a multi-layer perfect wave-absorbing cement sheet to achieve the characteristics of efficient absorption of electromagnetic waves in a specific frequency band.

Benefits of technology

It realizes efficient absorption of electromagnetic waves in a wide frequency range, has high absorption rate, wide working frequency bandwidth, simple preparation process, good load-bearing and durable performance, reduces cost, and is suitable for a wide range of applications of building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113285231B_ABST
    Figure CN113285231B_ABST
Patent Text Reader

Abstract

The present invention discloses a multi-layer perfect wave-absorbing cement board, comprising a periodic surface layer, a load-bearing wave-absorbing medium layer, a lower medium layer and a shielding bottom plate stacked in sequence; carbon nanotubes are used in the periodic surface layer and the load-bearing wave-absorbing medium layer at the same time; the periodic surface layer is composed of a periodically arranged conductive surface on a wave-transparent substrate; the load-bearing wave-absorbing medium layer is a medium layer formed by a cement-based material mixed with a carbon nanotube wave-absorbing agent; the lower medium layer is a wave-transparent medium plate; the shielding bottom plate is a metal bottom plate or a plane made of a conductive material that reflects electromagnetic waves. The present invention combines super-surface technology to integrate building materials into the medium layer of the super-surface structure, thereby realizing a wave-absorbing super-structure material that can bear weight. It has high absorption rate, wide working frequency band, simple preparation process, and good load-bearing and durability performance. Compared with other wave-absorbing materials with similar performance on the market, it has the advantages of low cost, load-bearing and fireproof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building wave-absorbing structures, and specifically to a multi-layer perfect wave-absorbing cement board, which is based on super-surface technology and cement-based material mixing technology, mixes building materials and nano-materials, and integrates them into a structure of super-structure materials, and has the characteristic of perfectly absorbing electromagnetic waves. Background Art

[0002] Due to the rapid growth of radio communications and electronic equipment applications, electromagnetic wave radiation has become a new pollution. Electromagnetic interference not only affects the operation of various electronic devices, but also directly affects the human body and even promotes the growth of tumors. Therefore, in the field of building structures, the absorption of electromagnetic waves has attracted the attention of researchers. The absorption performance of traditional building materials, such as cement-based materials, is mainly achieved by adding absorbers to building materials. However, the current research on building absorbing materials mainly focuses on mixing absorbers into cement-based materials through mixing processes.

[0003] The effect of enhancing the absorbing performance of this traditional method depends on the absorbing performance of each component of the cement-based material itself, and it is necessary to determine the best choice and the most appropriate dosage of the absorber through continuous ratio tests. Therefore, its shortcomings are also obvious. First, fundamentally speaking, the absorbing performance of cement-based materials depends on the arrangement characteristics of the material molecules themselves, and it is impossible to control the specific absorption characteristics through artificial design. Therefore, the process of researchers designing absorbing materials is passive, and the absorbing performance of the prepared materials cannot be actively controlled. Second, researchers must try to find materials whose natural impedance matches the free space. However, materials that match the natural impedance are required to be close to the air impedance, and most of them are loose and porous materials, which does not conform to the design idea of ​​strengthening and toughening building materials. Third, the preparation of this kind of absorbing material is greatly affected by factors such as materials, environment, and maintenance in various places, and it is difficult to achieve industrialized and unified production. Fourth, compared with advanced electromagnetic absorbing structures, this method has a very limited effect on improving absorbing performance.

[0004] Electromagnetic metamaterials (metamaterials) provide an ideal solution to the above problems. Metamaterials and metasurfaces are a rapidly developing topic in recent years. Metamaterials not only have unique electromagnetic properties, but also have broad application prospects. Metasurfaces can be artificially designed to work at all sub-optical wave frequencies, and have proven their feasibility in microwave, millimeter wave, terahertz, infrared and near-infrared ranges. Through artificial design, it can achieve nearly 100% electromagnetic wave absorption in a specific frequency band, showing perfect absorption characteristics. In addition, after the metamaterial design is completed, it can be mass-produced in a unified manner to ensure stable performance.

[0005] However, the current electromagnetic metasurfaces are delicate to produce and relatively complex to process, and they do not have load-bearing, fire-proof, and durable functions, and cannot be directly used in building structures. In addition, the materials used in construction do not have the electromagnetic properties required by the surface layers and dielectric layers of metamaterials, and cannot be integrated into metasurfaces and metamaterial structures. In the field of metamaterials, there are the following technical biases, which make it an obstacle to the application of metamaterials in cement structures: (1) The period length of the metal layer on the surface is generally at the micron level. Due to process and cost reasons, cement structure production cannot mass-produce such surfaces; (2) To ensure accuracy, the surface metal layer needs to be etched, optically printed, etc., which is also not suitable for cement production; (3) The dielectric layer used in metamaterials is a completely wave-transmitting material, while cement materials can only achieve a transmission of about 30%-70%, which is obviously not within the selection range of metamaterials’ wave-transmitting media. These technical biases and manufacturing difficulties have become a problem in the combination of metamaterials and building absorbing structures. There is currently no relevant solution. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a multi-layer perfect absorbing cement board. The carbon nanotube absorber is first mixed with a cement-based material, and then the cement-based material is integrated into a dielectric layer of a super-surface structure using carbon nanotubes as a conductive surface, to achieve a perfect load-bearing absorbing super-structure material; it has a high absorption rate, a wide working frequency band, a simple preparation process, and good load-bearing and durability performance.

[0007] To this end, the present invention adopts the following technical solutions:

[0008] A multi-layer perfect wave-absorbing cement board comprises a periodic surface layer, a load-bearing wave-absorbing medium layer, a lower medium layer and a shielding bottom plate which are stacked in sequence from top to bottom; carbon nanotubes are used in both the periodic surface layer and the load-bearing wave-absorbing medium layer; the periodic surface layer is a structure of periodic conductive surfaces arranged on a wave-transparent substrate; the load-bearing wave-absorbing medium layer is a cement-based material mixed with a carbon material wave-absorbing agent; the lower medium layer is a wave-transparent medium board; the shielding bottom plate is a metal bottom plate or a plane made of a conductive material which completely reflects electromagnetic waves; the bandwidth of perfectly absorbing electromagnetic waves accounts for no less than 90% of the total bandwidth.

[0009] Furthermore, the periodic surface layer is composed of a periodic conductive surface arranged on a wave-transmitting substrate. The wave-transmitting substrate is a ceramic fiber board with a wave transmittance greater than 95%, a dielectric constant less than 10, and a thickness of 0.01 mm-30 mm. The periodic conductive layer on the wave-transmitting substrate is prepared by a special preparation method of slurry. The periodic conductive surface on the wave-transmitting substrate is a carbon nanotube conductive surface, which is striped.

[0010] Furthermore, the arrangement of the periodic surface is a stripe array and the like. The size of the period is 5-100 mm, which is much larger than the conventional super surface period size (generally several microns), which is convenient for cement industry production and can meet the perfect absorption characteristics of cement boards. The width of each carbon nanotube conductive surface is 2.5 to 50 mm, and the period length in the periodic surface layer is 5 to 100 mm. Preferably, the width of each carbon nanotube conductive surface is 8 to 16 mm, and the period length in the periodic surface layer is 16 to 32 mm. Most preferably, the width of each carbon nanotube conductive surface is 12 mm, and the period length in the periodic surface layer is 24 mm.

[0011] Furthermore, the preparation method of the periodically arranged conductive layer is as follows: using nanotube material, and then using a mold-squeeze method to cover the wave-transparent substrate. The specific implementation is as follows:

[0012] Prepare a striped hollow mold and cover the mold on a ceramic fiberboard. To prevent the slurry from flowing into the gap between the mold and the fiberboard due to capillary phenomenon, the mold should be raised by 1-5 cm with a gasket;

[0013] Use a syringe to absorb the slurry and squeeze it into the mold along the hollow;

[0014] Immediately use a brush to evenly apply the squeezed slurry (nanotube material) to the hollowed-out parts of the mold;

[0015] Remove the mold.

[0016] This preparation method breaks through the conventional technical prejudice, because the current super surface preparation requires the use of solid metals, such as gold, copper and other materials through etching, optical printing and other methods, which cannot be used in cement production.

[0017] Furthermore, the load-bearing absorbing medium layer is a cement-based material, which is mixed with a carbon nanotube absorber, and the absorber is further mixed into the load-bearing absorbing medium layer, and the mixing amount is 0.01wt.%-20wt.%, that is, the mass ratio of the cement-based material to the carbon nanotube absorber is 0.01-20:100. The compressive strength of the load-bearing absorbing medium layer is greater than 30MPa. The thickness is 1-50mm. It should be noted that the cement substrate mixed with the absorber has strong absorption performance and greatly weakened wave transmission performance, which directly breaks through the existing technical prejudice. Because in the field of absorbing material technology, the medium layer selected for metamaterials and metasurfaces should be a wave-transmitting material. The present invention breaks through this limitation through technical innovation design, and integrates the wave-absorbing cement substrate, which is not completely wave-transmitting, into the metamaterial, which significantly improves the wave-absorbing performance of cement-based materials.

[0018] Furthermore, the lower dielectric layer is a wave-transmitting material with a dielectric constant of less than 10 and a thickness of 0.01-30 mm, including but not limited to mineral fiber boards, polytetrafluoroethylene boards, silicon-based materials and other building materials that can transmit electromagnetic waves.

[0019] Furthermore, the shielding bottom plate should completely reflect electromagnetic waves (reflectivity is 100%), including but not limited to metal plates with good conductivity, metal foils, flat substrates made of conductive materials, etc. The thickness of the shielding bottom plate should be as thin as possible, preferably 0.1-10 mm. Complete reflection of electromagnetic waves means a reflectivity of 100%.

[0020] Furthermore, the multi-layer perfect absorbing plate has the characteristics of wide-band and efficient absorption of radar waves, and should meet the following requirements: within the radiation frequency band (which should be divided into L-band, S-band, C-band, X-band, Ku-band, etc.), the relative bandwidth of perfect absorption (the ratio of the bandwidth with an absorption rate greater than 97% to the total bandwidth) should not be less than 90% of the total bandwidth of the band.

[0021] The present invention combines metasurface technology to integrate building materials into the dielectric layer of the metasurface structure, thereby realizing a load-bearing absorbing metastructure material. It has high absorption rate, wide working frequency band, simple preparation process, good load-bearing and durability performance. Compared with other absorbing materials with similar performance on the market, it has the advantages of low cost, load-bearing and fireproof.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) Comparison of wave absorption performance with similar cement-based absorbing materials: The reflectivity of similar cement-based absorbing materials cannot reach below -15dB (absorption rate 97%) in a wide frequency range, and -10dB (absorption rate 90%) is generally used as a criterion for good absorption performance. According to literature research, the best performance of cement-based absorbing materials at present is that the bandwidth with an absorption rate greater than 97% accounts for less than 30% of the total bandwidth. The indicator of the present invention can reach more than 90%, or even close to 100% (see the embodiment).

[0024] (2) Cost of this project: including material costs and labor costs for floors 1-4 (the specific materials are calculated according to the materials used in the example), the unit price is 300 yuan / m 2 Within.

[0025] (3) Comparison of performance and cost with several major absorbing materials on the market:

[0026] At present, the absorbing materials on the market mainly rely on foam porous structures to absorb a large amount of waves, and apply absorbing agents on the substrate to make absorbing surfaces, and super surface regulation to absorb waves. The foam porous structure is low in cost, but it takes up a lot of space and cannot hold force. The absorbing tape is thin and soft and can be attached to the surface of the structure, but it is not resistant to high temperatures. The silicone rubber sheet absorbing material can work at 200°C, but the cost is high. It is mainly used in key and small parts. The size of each piece is about 30cm×20cm, and the unit price is about 3,000 yuan per piece (that is, more than 10,000 yuan per square meter). Using the technology provided by the present invention, the cost can be reduced by dozens of times.

[0027] These absorbing materials are mainly used in the field of communications and can achieve perfect absorption in certain frequency bands, but they cannot be used as bearing components and are expensive. The cement-based absorbing materials currently used in the construction field have very limited absorbing performance and are difficult to achieve perfect absorption levels. The applicable bandwidth is relatively narrow. This invention introduces the concept of metamaterials into concrete structures for the first time, greatly improving the absorbing performance of concrete materials. It also uses ordinary building fireproof materials and a very small amount of conductive slurry to prepare metasurfaces, which greatly reduces the cost and makes it possible to use concrete absorbing structures in large quantities in engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the structure of the multi-layer perfect wave-absorbing cement board of the present invention;

[0029] Figure 2 This is a top front view of the structure of the multi-layer perfect wave-absorbing cement board of the present invention;

[0030] Figure 3 is a reflectivity curve diagram of the wave absorbing structure in Example 1;

[0031] Figure 4 It is a reflectivity curve diagram of the wave absorbing structure in Example 2. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It should be understood that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unspecified implementation conditions are usually the conditions in routine experiments.

[0033] Example 1

[0034] Reference Figure 1The preparation of the multi-layer perfect wave absorbing plate of this embodiment is as follows: the wave-transmitting substrate of the periodic surface layer 1 is a ceramic fiber board with a thickness of 5 mm, and the board is coated with a carbon nanotube periodic super surface layer with a thickness of 0.01 mm. The shape of the super surface is striped, and the coating is equidistant, such as Figure 2 As shown, the stripe period T is 24 mm, the stripe width D and the spacing L are both 12 mm; the specific preparation is as follows:

[0035] Prepare a stripe hollow mold with a hollow width of 12 mm, cover the mold on a ceramic fiberboard, and raise the mold by 4 cm with a gasket to prevent the slurry from flowing into the gap between the mold and the fiberboard due to capillary phenomenon;

[0036] Use a syringe to absorb the slurry and squeeze it into the mold along the hollow;

[0037] Immediately use a 10mm wide brush to evenly apply the squeezed slurry (carbon nanotube material) to the hollow parts of the mold;

[0038] Remove the mold.

[0039] The thickness of the load-bearing absorbing medium layer 2 is a cement substrate of 25 mm. 0.5 wt.% multi-walled carbon nanotubes are added to the cement-based material, that is, the mass ratio of multi-walled carbon nanotubes to cement-based materials is 0.5:100, the length of the carbon nanotubes is 3-10 μm, the diameter is 30-40 nm, and the compressive strength of the load-bearing absorbing medium layer 2 is 40 MPa. The lower dielectric layer 3 is a ceramic fiberboard with a thickness of 5 mm; the substrate 4 (i.e., the shielding bottom plate) is a copper plate that completely reflects electromagnetic waves, and the thickness of the copper plate is 5 mm. The 1st, 2nd, 3rd, and 4th layers are bonded with epoxy resin.

[0040] The effectiveness of the embodiment is verified in the Ku band (12-18 GHz). Its absorbing performance is expressed by reflectivity. The reflectivity of the specimen in the range of 12-18 GHz is tested by the bow method. Figure 3 As shown. The reflectivity of this embodiment is very stable in the Ku band, all below -14.9dB. The perfect absorption frequency band, that is, the frequency band with a reflectivity less than -15dB, is 12-11.92GHz, and the relative bandwidth of perfect absorption (the ratio of the bandwidth with an absorption rate greater than 97% to the total bandwidth) is 98.7%.

[0041] Example 2

[0042] Reference Figure 1 The preparation of the multi-layer perfect wave absorbing plate of this embodiment is as follows: the wave-transmitting substrate of the periodic surface layer 1 is a ceramic fiber board with a thickness of 5 mm, and a carbon nanotube periodic super surface layer with a thickness of 0.01 mm is coated on the board. The shape of the super surface is striped and coated at equal intervals, such as Figure 2As shown, the stripe period T is 24 mm, the stripe width D and the spacing L are both 12 mm; the specific preparation is as follows:

[0043] Prepare a stripe hollow mold with a hollow width of 12 mm, cover the mold on a ceramic fiberboard, and raise the mold by 4 cm with a gasket to prevent the slurry from flowing into the gap between the mold and the fiberboard due to capillary phenomenon;

[0044] Use a syringe to absorb the slurry and squeeze it into the mold along the hollow;

[0045] Immediately use a 10mm wide brush to evenly apply the squeezed slurry to the hollow parts of the mold;

[0046] Remove the mold.

[0047] The load-bearing absorbing medium layer 2 is a cement substrate with a thickness of 25 mm, mixed with 1.0 wt.% multi-walled carbon nanotubes, the length of the carbon nanotubes is 3-10 μm, and the diameter is 30-40 nm. The compressive strength of the load-bearing absorbing medium layer is 40 MPa. The lower medium layer 3 is a ceramic fiberboard with a thickness of 5 mm; the substrate 4 is a copper plate that completely reflects electromagnetic waves, and the thickness of the copper plate is 5 mm. The 1st, 2nd, 3rd, and 4th layers are bonded with epoxy resin.

[0048] The effectiveness of the embodiment is verified in the Ku band (12-18 GHz). Its absorbing performance is expressed by reflectivity. The reflectivity of the specimen in the range of 12-18 GHz is tested by the bow method. Figure 4 As shown. The reflectivity of this embodiment in the Ku band is all lower than -16.1dB (the absorption rate is all greater than 97%). Therefore, the relative bandwidth of perfect absorption is 100%. In addition, the reflectivity of this embodiment in the range of 12-16.3GHz is less than -20dB, showing excellent electromagnetic wave absorption performance.

[0049] The present invention has been described in detail above. The above embodiments are only preferred embodiments of the present invention, which are used to help understand the method and core ideas of the present invention. The purpose is to enable people familiar with the technology in this field to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any modification, equivalent change or improvement made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-layer perfect wave-absorbing cement board, characterized by: It comprises a periodic surface layer (1), a load-bearing wave-absorbing medium layer (2), a lower medium layer (3) and a shielding bottom plate (4) which are stacked in sequence; The periodic surface layer (1) is composed of a periodically arranged conductive surface on a wave-transmitting substrate, wherein the periodically arranged conductive surface on the wave-transmitting substrate is a carbon nanotube conductive surface in the form of stripes; The load-bearing absorbing medium layer (2) is a medium layer formed of a cement-based material mixed with a carbon nanotube absorbing agent; The lower dielectric layer (3) is a wave-transmitting dielectric plate, the wave-transmitting dielectric plate having a dielectric constant less than 10 and a thickness of 0.01-30 mm; The shielding bottom plate (4) is a metal bottom plate that reflects electromagnetic waves or a plane made of a conductive material.

2. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The wave-transmitting substrate is a ceramic fiberboard with a wave transmittance of more than 95%.

3. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The wave-transmitting substrate has a dielectric constant of less than 10 and a thickness of 0.01 mm to 30 mm.

4. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The width of each carbon nanotube conductive surface is 2.5-50 mm, and the period length in the periodic surface layer is 5-100 mm.

5. The multi-layer perfect wave-absorbing cement board according to claim 4, characterized in that: The width of each carbon nanotube conductive surface is 8-16 mm, and the period length in the periodic surface layer is 16-32 mm.

6. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The preparation of the periodic surface layer is as follows: nanotube material is used and then covered on the wave-transparent substrate by a mold-squeezing method.

7. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The load-bearing wave-absorbing medium layer (2) has a thickness of 1-50 mm.

8. The multi-layer perfect wave-absorbing cement board according to claim 1, characterized in that: The thickness of the shielding bottom plate is 0.1-10 mm.

Citation Information

Patent Citations

  • Multilayer perfect wave-absorbing cement board

    CN215579075U